Research Trends of Quality Assurance in Islamic Education: A Bibliometric Analysis - Nasrudin, Dindin; Rochman, Chaerul; Kuntadi, Dedi; Jamaluddin, Dindin (Journal of Quality Assurance in Islamic Education (JQAIE), 2021)
Quality Assurance (QA) has an important role in improving the quality of Islamic Education. This study aims to reveal the trend of QA research in Islamic Education based on the research results of the last 20 years (2000-2021) from the Scopus database and the last 5 years from the Google Scholar (GS) database. The research method used was bibliometric analysis. Search articles using Publish or Perish (PoP) software using the keywords “Quality Assurance in Education” from the Scopus database and “Quality Assurance” AND “Islamic Education” from the GS database. The number of papers collected from the Scopus database was 68, which the paper selected to 28. From the GS database, 981 papers were selected to be 39, so that the total number of papers analyzed was 67. The analysis process used the Mendeley reference management software, which was visualized by the VOSviewer software. Overall, this study shows the most influential authors in the QA field, research trends, and research opportunities in the field of Quality Assurance in Islamic Education